PROCEDURES OF LAND DISPUTES SETTLEMENTS IN TOWANI TOLOTANG TRADITIONAL COMMUNITY IN SIDRAP REGENCY - Ansaar, Ansaar; Bahtiar, Bahtiar (Walasuji : Jurnal Sejarah dan Budaya, 2021)
This research is the result of field research which aimed to reveal the forms of land disputes that occurred in the territory of the Towani Tolotang customary community and the procedures for resolving them according to the customary provisions that implementeed in the customary community. This research was a qualitative descriptive using data collection techniques in the form of observations, interviews, and literature study. The study result indicated that the Towani Tolotang traditional community still implemented the old traditions, such as holding ritual ceremonies or traditional ceremonies based on the belief system they adhere to in their daily life. On the other hand, they also still implemented the customary rules or customary norms that have been outlined by their ancestors to be obeyed by all members of their followers. For example, when a land dispute occured, the settlements method was carried out by implementing the customary rules that have been passed down from their ancestors. Meanwhile, the form of land disputes that often occured in the area of the Towani Tolotang customary community was a dispute involving an individual with another individual or two parties who had family relation.